Preparation method of barium titanate doped corrosion-resistant high-entropy alloy composite wave-absorbing material

By doping barium titanate powder with high entropy alloy powder and ball milling and mixing, a composite absorbing material with excellent absorption performance and multi-band strong absorption characteristics was prepared, and the reflection loss value of existing absorbing materials was solved. Limited issues.

CN119457089APending Publication Date: 2025-02-18XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411595572.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The reflection loss value of existing absorbing materials is limited, making it difficult to achieve strong absorption in multiple bands.

Method used

By doping the barium titanate powder with a high-entropy alloy powder dominated by ferromagnetic elements, and using ball mill mixing to prepare a composite wave absorbing material. The method includes using agate balls in the ball milling tank, using anhydrous ethanol as the ball milling medium, and controlling the ball milling time and temperature to ensure uniform mixing of the material and efficient wave absorption performance.

Benefits of technology

It realizes excellent absorbing performance of composite absorbing materials, can show strong absorption effect in multiple bands, has high reflection loss value and wide effective absorbing frequency band, and has good corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457089A_ABST
    Figure CN119457089A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a barium titanate doped corrosion-resistant high-entropy alloy composite wave-absorbing material, which comprises the following steps: step 1, mixing BaCO3 and TiO2, and carrying out ball milling and drying to obtain powder; 2, pre-sintering the powder to obtain a barium titanate green body; 3, the barium titanate green body is sequentially subjected to grinding, ball milling and drying, and barium titanate powder is obtained; fourthly, spherical high-entropy alloy powder is prepared and subjected to vacuum ball milling and drying treatment, and flaky high-entropy alloy powder is obtained; and fifthly, the barium titanate powder and the flaky high-entropy alloy powder are subjected to ball-milling mixing treatment, and the composite wave-absorbing material is obtained. According to the preparation method, the barium titanate material with the strong dielectric property is adopted and doped with the high-entropy alloy powder, the composite wave-absorbing material with the excellent wave-absorbing performance is obtained, and the composite wave-absorbing material is suitable for the field of wave-absorbing coatings in seawater and chemical industry extreme service environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave absorbing materials, and in particular relates to a method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite microwave absorbing material. Background Art

[0002] Barium titanate is a strong dielectric compound material with excellent dielectric properties. Studies have shown that barium titanate can be combined with carbon-based materials or magnetic ferrites, which may show broad application prospects in the field of microwave absorption.

[0003] The Chinese invention patent "Preparation Method of High Absorption Performance Nano Barium Titanate / Fe3O4 Hybrid Material" (Announcement No. CN113329608B) synthesizes BaTiO3 powder with a particle size of 10nm to 500nm, and directly deposits nano Fe3O4 particles in situ on the surface of nano BaTiO3 to form hybrid material powder. Nano Fe3O4 forms a surface contact on the surface of nano BaTiO3 to produce a large number of interfaces. Due to the accumulation of a large number of defects and ions on both sides of the interface, an electromagnetic wave barrier is formed, which strongly absorbs and scatters electromagnetic waves in various frequency bands. When the thickness of the material is 2mm, the reflection loss at a frequency of 2GHz can reach -9.84dB to -29.4dB, showing its potential application value in absorbing coatings or electromagnetic shielding materials, but there is still a problem of limited reflection loss value of absorbing performance.

[0004] Therefore, there is an urgent need to develop a method for preparing a composite material with excellent microwave absorbing properties. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a preparation method of a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material. The preparation method adopts a barium titanate material with strong dielectric properties and dopes it with a high-entropy alloy powder with ferromagnetic elements as the main element to obtain a composite absorbing material with excellent absorbing performance, thereby solving the problem of limited reflection loss value of existing absorbing materials.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material, characterized in that the preparation method comprises the following steps:

[0007] Step 1, mixing BaCO3 and TiO2, ball milling and drying to obtain powder;

[0008] Step 2: pre-sintering the powder obtained in step 1 to obtain a barium titanate green body;

[0009] Step 3, grinding, ball milling and drying the barium titanate green body obtained in step 2 in sequence to obtain barium titanate powder;

[0010] Step 4: preparing spherical high entropy alloy powder and performing vacuum ball milling and drying treatment in sequence to obtain lamellar high entropy alloy powder; the spherical high entropy alloy powder contains ferromagnetic elements as main elements;

[0011] Step 5: ball-mill the barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 to obtain a composite absorbing material.

[0012] The present invention first grinds the barium titanate green body until its powder has no obvious lumps, and then performs ball milling to make the powder particle size uniform and dispersed, so that the barium titanate powder can be uniformly mixed with the high entropy alloy powder.

[0013] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the ball milling in step one and step three uses a ball mill jar, the grinding balls in the ball mill jar are agate balls, the ball milling speed is 400r / min~500r / min, the ball milling time is 1h~3h, the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol used is 1 / 2~2 / 3 of the capacity of the ball mill jar.

[0014] The present invention adopts anhydrous ethanol as the ball milling medium and controls the amount thereof, thereby reducing the introduction of impurities and avoiding oxidation of raw materials; in addition, by adopting agate balls as grinding balls, it is possible to avoid the use of other materials such as stainless steel grinding balls, which may cause friction and collision between the grinding balls and the grinding jar during the ball milling process, thereby leading to the introduction of metal impurities.

[0015] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the amount of anhydrous ethanol used is 2 / 3 of the capacity of the ball mill.

[0016] The present invention controls the amount of anhydrous ethanol to 2 / 3 of the capacity of the ball mill, thereby preventing the anhydrous ethanol from gradually volatilizing during ball milling when the amount is small, thereby increasing the possibility of oxidation of the powder.

[0017] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the heating rate of the pre-sintering treatment in step 2 is 2°C / min to 5°C / min, the pre-sintering temperature is 1000°C to 1250°C, and the pre-sintering holding time is 3h to 5h.

[0018] The present invention controls the sintering temperature to 1000-1250°C, which is 2 / 3-4 / 5 of the melting point of the material, to avoid melting and bonding of the barium titanate green body; controls the powder reaction by controlling the heat preservation time, and thus obtains the barium titanate green body with higher purity.

[0019] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the spherical high-entropy alloy powder in step 4 is one of a FeMnCoNiCr high-entropy alloy, a FeCoCrNi high-entropy alloy and a FeCoCr high-entropy alloy.

[0020] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the spherical high-entropy alloy powder described in step four is prepared by a vacuum air atomization powder making process, the temperature of the vacuum air atomization powder making process is 1400°C to 1600°C, and the heating time of the vacuum air atomization powder making process is 50min to 80min.

[0021] The present invention controls the temperature of vacuum gas atomization powder making, which is beneficial to improving the powder forming rate of high entropy alloy powder and reducing raw material loss.

[0022] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the grinding balls of the vacuum ball mill in step 4 are stainless steel balls, the mass ratio of the stainless steel balls to the high-entropy alloy powder is 10:1 to 20:1, the vacuum ball milling time is 8h to 24h, the rotation speed of the vacuum ball mill is 400r / min to 600r / min, the process control agent of the vacuum ball mill is anhydrous ethanol, and the amount of anhydrous ethanol added is 10mL to 50mL.

[0023] The present invention can introduce surface polarization effect by flaking the powder, thereby improving the dielectric loss capacity of the material and ultimately improving the wave absorbing performance of the material; and can adjust the particle size by adding a process control agent during the ball milling process and controlling the amount of the process control agent to reduce the degree of cold welding.

[0024] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the ball milling treatment in step five adopts a dry milling process, the rotation speed of the ball milling treatment is 400r / min~600r / min, and the time of the ball milling treatment is 20min~60min.

[0025] The present invention adopts a dry grinding process to ball-mill barium titanate powder and flaked high entropy alloy powder. No process control agent is added during the dry grinding process. Under the action of thermal effect, the organic coupling of barium titanate and high entropy alloy powder can be accelerated, so that the composite absorbing material has better absorbing performance.

[0026] The above-mentioned method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material is characterized in that the composite absorbing material in step five is composed of 70% to 99% by mass of a high-entropy alloy and 1% to 30% by mass of barium titanate.

[0027] Through a large number of experiments and tests, the present invention has found that when the composite absorbing material is composed of 70% to 99% by mass of a high entropy alloy and 1% to 30% by mass of barium titanate, the composite absorbing material has better absorbing performance.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] 1. The present invention adopts barium titanate powder doped with high entropy alloy powder with ferromagnetic elements as the main element, and the obtained composite absorbing material has better absorbing performance than the existing absorbing materials, and can achieve strong absorption in multiple bands.

[0030] 2. The present invention can prepare barium titanate powder through chemical synthesis and simple ball milling and pre-sintering treatment processes, which simplifies the preparation process of barium titanate powder. The preparation equipment of barium titanate powder is partially the same as the equipment for preparing high entropy alloy powder, which can reduce equipment investment and reduce production costs.

[0031] 3. The composite absorbing material prepared by the present invention is used to prepare a coating. When the coating is thin, it has the characteristics of high absorption intensity, wide effective absorbing frequency band and strong absorption in multiple bands. In addition, the composite absorbing material also has excellent corrosion resistance and can maintain a certain absorbing ability in extreme service environments such as seawater and chemical industry.

[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a microscopic morphology of the composite absorbing material prepared in Example 1 of the present invention.

[0034] Figure 2 This is a graph showing the reflection loss test results of the composite absorbing material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] Example 1

[0036] The preparation method of this embodiment comprises the following steps:

[0037] Step 1: put 8.5417g of BaCO3 and 3.4583g of TiO2 into a ball mill, add 2 / 3 of the capacity of the ball mill as anhydrous ethanol as a ball milling medium, and ball mill for 3 hours, and obtain powder after drying; the ball mill speed is 500r / min, and the grinding balls in the ball mill are agate balls;

[0038] Step 2: placing the powder obtained in step 1 into a dried culture dish, and then placing the culture dish containing the powder in a muffle furnace for pre-sintering to obtain a barium titanate green body; the heating rate of the pre-sintering treatment is 2°C / min, the pre-sintering temperature is 1250°C, and the pre-sintering holding time is 3h;

[0039] Step 3: Grind the barium titanate green body obtained in step 2 with an agate mortar, then put it into a ball mill, add 2 / 3 of the capacity of the ball mill with anhydrous ethanol as a ball milling medium, and ball mill for 3 hours, and obtain barium titanate powder after drying; the ball mill speed is 500r / min, and the grinding balls in the ball mill are agate balls;

[0040] Step 4: weigh the raw materials according to the nominal composition of the FeMnCoNiCr high entropy alloy and prepare them into high entropy alloy ingots by using a suspension smelting furnace, and then prepare spherical FeMnCoNiCr high entropy alloy powder by using a vacuum gas atomization powder making process, and perform vacuum ball milling and drying to obtain lamellar high entropy alloy powder; the temperature of the vacuum gas atomization powder making process is 1530°C, and the heating time is 70min; the grinding balls of the vacuum ball mill are stainless steel balls, the mass ratio of the stainless steel balls to the high entropy alloy powder is 15:1, the vacuum ball milling time is 24h, the vacuum ball milling speed is 480r / min, and the process control agent of the vacuum ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 20mL;

[0041] Step 5. The barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 are ball-milled and mixed to obtain a composite absorbing material; the ball milling is a dry milling process, the ball milling speed is 480 r / min, the ball milling time is 30 min, and the composite absorbing material consists of 85% by mass of FeMnCoNiCr high entropy alloy and 15% by mass of barium titanate.

[0042] The composite absorbing material prepared in this embodiment is subjected to microscopic morphology analysis. Figure 1 As shown, the composite absorbing material has a sheet-like structure.

[0043] The reflection loss test of the composite absorbing material prepared in this embodiment is carried out, and the results are as follows: Figure 2 As shown in the figure, when the simulated thickness of the composite absorbing material is 1.4 mm, the minimum reflection loss is -37.2 dB, the effective absorbing bandwidth is about 3 GHz, and there are reflection loss peaks in many places in the 1 GHz to 18 GHz band. The corrosion current density of the composite absorbing material measured by the electrochemical test method is about 1×10 -5 A / cm 2 , the corrosion potential is about -60mV.

[0044] In summary, the composite absorbing material prepared in this embodiment has the characteristics of high absorption intensity, wide effective absorbing frequency band, strong absorption in multiple bands and corrosion resistance.

[0045] Example 2

[0046] The preparation method of this embodiment comprises the following steps:

[0047] Step 1: put 8.5417g of BaCO3 and 3.4583g of TiO2 into a ball mill, add 2 / 3 of the capacity of the ball mill as anhydrous ethanol as a ball milling medium, and ball mill for 2h, and obtain powder after drying; the ball mill speed is 400r / min, and the grinding balls in the ball mill are agate balls;

[0048] Step 2: placing the powder obtained in step 1 into a dried culture dish, and then placing the culture dish containing the powder in a muffle furnace for pre-sintering to obtain a barium titanate green body; the heating rate of the pre-sintering treatment is 2°C / min, the pre-sintering temperature is 1000°C, and the pre-sintering holding time is 5h;

[0049] Step 3: Grind the barium titanate green body obtained in step 2 with an agate mortar, then put it into a ball mill, add 2 / 3 of the capacity of the ball mill with anhydrous ethanol as a ball milling medium, and ball mill for 5 hours, and obtain barium titanate powder after drying; the ball mill speed is 400r / min, and the grinding balls in the ball mill are agate balls;

[0050] Step 4: weigh the raw materials according to the nominal composition of the FeCoCrNi high entropy alloy and prepare them into high entropy alloy ingots by a suspension smelting furnace, and then prepare them into spherical FeCoCrNi high entropy alloy powders by a vacuum gas atomization powder making process, and perform vacuum ball milling and drying to obtain lamellar high entropy alloy powders; the temperature of the vacuum gas atomization powder making process is 1450° C., and the heating time is 80 min; the grinding balls of the vacuum ball mill are stainless steel balls, and the mass ratio of the stainless steel balls to the high entropy alloy powder is 20:1, the vacuum ball milling time is 12 h, the vacuum ball milling speed is 600 r / min, and the process control agent of the vacuum ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 10 mL;

[0051] Step 5. The barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 are ball-milled and mixed to obtain a composite absorbing material; the ball milling is a dry milling process, the ball milling speed is 400r / min, the ball milling time is 60min, and the composite absorbing material consists of 90% by mass of FeCoCrNi-based high entropy alloy and 10% by mass of barium titanate.

[0052] After inspection, when the thickness of the composite absorbing material prepared in this embodiment is 2.1 mm, the minimum reflection loss is -23 dB, the effective absorbing bandwidth is about 2 GHz, and there are reflection loss peaks at multiple locations in the 1 GHz to 18 GHz band; the corrosion current density of the composite absorbing material measured by the electrochemical test method is about 6.1×10 -4 A / cm 2 , the corrosion potential is about -45mV.

[0053] In summary, the composite absorbing material prepared in this embodiment has the characteristics of high absorption intensity, wide effective absorbing frequency band, strong absorption in multiple bands and corrosion resistance.

[0054] Example 3

[0055] The preparation method of this embodiment comprises the following steps:

[0056] Step 1: put 8.5417g of BaCO3 and 3.4583g of TiO2 into a ball mill, add 2 / 3 of the capacity of the ball mill as anhydrous ethanol as a ball milling medium, and ball mill for 2h, and obtain powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0057] Step 2: placing the powder obtained in step 1 into a dried culture dish, and then placing the culture dish containing the powder in a muffle furnace for pre-sintering to obtain a barium titanate green body; the heating rate of the pre-sintering treatment is 2°C / min, the pre-sintering temperature is 1100°C, and the pre-sintering holding time is 4h;

[0058] Step 3: Grind the barium titanate green body obtained in step 2 with an agate mortar, then put it into a ball mill, add 2 / 3 of the capacity of the ball mill with anhydrous ethanol as a ball milling medium, and ball mill for 4 hours, and obtain barium titanate powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0059] Step 4: weigh the raw materials according to the nominal composition of the FeCoCr high entropy alloy and prepare them into high entropy alloy ingots by a suspension smelting furnace, and then prepare them into spherical FeCoCr high entropy alloy powders by a vacuum gas atomization powder making process, and perform vacuum ball milling and drying to obtain lamellar high entropy alloy powders; the temperature of the vacuum gas atomization powder making process is 1480° C., and the heating time is 50 min; the grinding balls of the vacuum ball mill are stainless steel balls, the mass ratio of the stainless steel balls to the high entropy alloy powder is 10:1, the vacuum ball milling time is 20 h, the vacuum ball milling speed is 420 r / min, and the process control agent of the vacuum ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 30 mL;

[0060] Step 5. The barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 are ball-milled and mixed to obtain a composite absorbing material; the ball milling is a dry milling process, the ball milling speed is 600r / min, the ball milling time is 20min, and the composite absorbing material consists of 80% by mass of FeCoCr-based high entropy alloy and 20% by mass of barium titanate.

[0061] After inspection, when the thickness of the composite absorbing material prepared in this embodiment is 1 mm, the minimum reflection loss is -45 dB, the effective absorbing bandwidth is about 3.4 GHz, and there are reflection loss peaks at multiple locations in the 1-18 band; the corrosion current density of the composite absorbing material measured by the electrochemical test method is about 4.2×10 -4 A / cm 2 , the corrosion potential is about -31mV.

[0062] In summary, the composite absorbing material prepared in this embodiment has the characteristics of high absorption intensity, wide effective absorbing frequency band, strong absorption in multiple bands and corrosion resistance.

[0063] Example 4

[0064] The preparation method of this embodiment comprises the following steps:

[0065] Step 1: put 8.5417g of BaCO3 and 3.4583g of TiO2 into a ball mill, add 2 / 3 of the capacity of the ball mill as anhydrous ethanol as a ball milling medium, and ball mill for 1 hour, and obtain a powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0066] Step 2: placing the powder obtained in step 1 into a dried culture dish, and then placing the culture dish containing the powder in a muffle furnace for pre-sintering to obtain a barium titanate green body; the heating rate of the pre-sintering treatment is 5°C / min, the pre-sintering temperature is 1000°C, and the pre-sintering holding time is 5h;

[0067] Step 3: Grind the barium titanate green body obtained in step 2 with an agate mortar, then put it into a ball mill, add 2 / 3 of the capacity of the ball mill with anhydrous ethanol as a ball milling medium, and ball mill for 5 hours, and obtain barium titanate powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0068] Step 4: weigh the raw materials according to the nominal composition of the FeMnCoNiCr high entropy alloy and prepare them into high entropy alloy ingots by a suspension smelting furnace, and then prepare them into spherical FeMnCoNiCr high entropy alloy powders by a vacuum gas atomization powder making process, and perform vacuum ball milling and drying to obtain lamellar high entropy alloy powders; the temperature of the vacuum gas atomization powder making process is 1400° C., and the heating time is 50 min; the grinding balls of the vacuum ball mill are stainless steel balls, the mass ratio of the stainless steel balls to the high entropy alloy powder is 15:1, the vacuum ball milling time is 8 h, the vacuum ball milling speed is 450 r / min, and the process control agent of the vacuum ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 20 mL;

[0069] Step 5. The barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 are ball-milled and mixed to obtain a composite absorbing material; the ball milling is a dry milling process, the ball milling speed is 500r / min, the ball milling time is 30min, and the composite absorbing material consists of 70% by mass of FeMnCoNiCr high entropy alloy and 30% by mass of barium titanate.

[0070] After inspection, when the thickness of the composite absorbing material prepared in this embodiment is 1.2 mm, the minimum reflection loss is -35 dB, the effective absorbing bandwidth is about 2.6 GHz, and there are reflection loss peaks at multiple locations in the 1-18 band; the corrosion current density of the composite absorbing material measured by the electrochemical test method is about 3.6×10 -4 A / cm 2 , the corrosion potential is about -72mV.

[0071] In summary, the composite absorbing material prepared in this embodiment has the characteristics of high absorption intensity, wide effective absorbing frequency band, strong absorption in multiple bands and corrosion resistance.

[0072] Example 5

[0073] The preparation method of this embodiment comprises the following steps:

[0074] Step 1: put 8.5417g of BaCO3 and 3.4583g of TiO2 into a ball mill, add 1 / 2 of the capacity of the ball mill as anhydrous ethanol as a ball milling medium, and ball mill for 1 hour, and obtain a powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0075] Step 2: placing the powder obtained in step 1 into a dried culture dish, and then placing the culture dish containing the powder in a muffle furnace for pre-sintering to obtain a barium titanate green body; the heating rate of the pre-sintering treatment is 3°C / min, the pre-sintering temperature is 1000°C, and the pre-sintering holding time is 5h;

[0076] Step 3: Grind the barium titanate green body obtained in step 2 with an agate mortar, then put it into a ball mill, add 1 / 2 of the capacity of the ball mill with anhydrous ethanol as a ball milling medium, and ball mill for 5 hours, and obtain barium titanate powder after drying; the ball mill speed is 480r / min, and the grinding balls in the ball mill are agate balls;

[0077] Step 4: weigh the raw materials according to the nominal composition of the FeCoCr high entropy alloy and prepare them into high entropy alloy ingots by a suspension smelting furnace, and then prepare them into spherical FeCoCr high entropy alloy powders by a vacuum gas atomization powder making process, and perform vacuum ball milling and drying to obtain lamellar high entropy alloy powders; the temperature of the vacuum gas atomization powder making process is 1600° C., and the heating time is 50 min; the grinding balls of the vacuum ball mill are stainless steel balls, the mass ratio of the stainless steel balls to the high entropy alloy powder is 15:1, the vacuum ball milling time is 8 h, the vacuum ball milling speed is 400 r / min, and the process control agent of the vacuum ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 50 mL;

[0078] Step 5. The barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 are ball-milled and mixed to obtain a composite absorbing material; the ball milling is a dry milling process, the ball milling speed is 450r / min, the ball milling time is 40min, and the composite absorbing material consists of 99% by mass of FeMnCoNiCr high entropy alloy and 1% by mass of barium titanate.

[0079] After inspection, when the thickness of the composite absorbing material prepared in this embodiment is 1.3 mm, the minimum reflection loss is -36 dB, the effective absorbing bandwidth is about 2.7 GHz, and there are reflection loss peaks at multiple locations in the 1-18 band; the corrosion current density of the composite absorbing material measured by the electrochemical test method is about 3.5×10 -4 A / cm 2 , the corrosion potential is about -70mV.

[0080] In summary, the composite absorbing material prepared in this embodiment has the characteristics of high absorption intensity, wide effective absorbing frequency band, strong absorption in multiple bands and corrosion resistance.

[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material, characterized in that: The preparation method comprises the following steps: Step 1, mixing BaCO3 and TiO2, ball milling and drying to obtain powder; Step 2: pre-sintering the powder obtained in step 1 to obtain a barium titanate green body; Step 3, grinding, ball milling and drying the barium titanate green body obtained in step 2 in sequence to obtain barium titanate powder; Step 4: preparing spherical high entropy alloy powder and performing vacuum ball milling and drying treatment in sequence to obtain lamellar high entropy alloy powder; the spherical high entropy alloy powder contains ferromagnetic elements as the main elements; Step 5: ball-milling the barium titanate powder obtained in step 3 and the flaky high entropy alloy powder obtained in step 4 to obtain a composite absorbing material.

2. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The ball mills in step 1 and step 3 are both made of a ball mill jar, the grinding balls in the ball mill jar are all agate balls, the ball mill speed is 400r / min~500r / min, the ball milling time is 1h~3h, the ball milling medium is all anhydrous ethanol, and the amount of anhydrous ethanol used is 1 / 2~2 / 3 of the capacity of the ball mill jar.

3. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 2, characterized in that: The amount of anhydrous ethanol used is 2 / 3 of the capacity of the ball mill.

4. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The heating rate of the pre-firing treatment in step 2 is 2°C / min to 5°C / min, the pre-firing temperature is 1000°C to 1250°C, and the pre-firing insulation time is 3h to 5h.

5. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The spherical high entropy alloy powder in step 4 is one of FeMnCoNiCr high entropy alloy, FeCoCrNi high entropy alloy and FeCoCr high entropy alloy.

6. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The spherical high entropy alloy powder described in step 4 is prepared by a vacuum air atomization powder making process, the temperature of the vacuum air atomization powder making process is 1400° C. to 1600° C., and the heating time of the vacuum air atomization powder making process is 50 min to 80 min.

7. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The grinding balls of the vacuum ball mill in step 4 are stainless steel balls, the mass ratio of the stainless steel balls to the high entropy alloy powder is 10:1 to 20:1, the vacuum ball milling time is 8h to 24h, the speed of the vacuum ball mill is 400r / min to 600r / min, the process control agent of the vacuum ball mill is anhydrous ethanol, and the amount of anhydrous ethanol added is 10mL to 50mL.

8. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The ball milling treatment in step 5 adopts a dry milling process, the rotation speed of the ball milling treatment is 400r / min to 600r / min, and the time of the ball milling treatment is 20min to 60min.

9. The method for preparing a barium titanate-doped corrosion-resistant high-entropy alloy composite absorbing material according to claim 1, characterized in that: The composite absorbing material in step five is composed of 70% to 99% by mass of a high entropy alloy and 1% to 30% by mass of barium titanate.

Citation Information

Patent Citations

  • Preparation method of high-absorption barium titanate / iron oxide nano-material

    CN113329608B